Integrated bioinformatics analysis identifies CHAD association with osteoporosis and in vitro chondrogenic effects of Wogonin - Keng-Fu Lan; Wei-Hsiang Su; Yongjin Zhong; Yan Wu; Siqi Ye; Dan He; Yancheng Lai; Charles C. N. Wang; Anchun Mo (Scientific Reports)
Abstract Osteoporosis (OP), characterized by reduced bone density and increased fracture risk. Current therapies have limitations due to side effects and variable efficacy, necessitating exploration of novel therapeutic targets and alternatives like Traditional Chinese Medicine (TCM). The molecular mechanisms driving OP remain incompletely understood. This study utilized integrated bioinformatics approaches to identify potentially dysregulated genes in OP and explored in vitro effects of TCM compounds targeting top identified genes. Differentially expressed genes (DEGs) associated with OP were identified by integrating bulk and single-cell RNA sequencing datasets. Potential therapeutic compounds targeting selected DEGs were screened from a TCM database using molecular docking to predict binding affinities. Based on highest binding scores, two compounds were selected for experimental validation. Their effects on chondrogenic differentiation, relevant to the known function of the identified target genes CHAD and COL2A1, were assessed in vitro using ATDC5 cells. Integrated bioinformatics analysis consistently identified CHAD and COL2A1 as significantly downregulated genes in OP datasets, and they were upregulated after teriparatide injection. Molecular docking predicted binding affinities of several TCM compounds to CHAD and COL2A1, with tetrandrine and wogonin showing the highest binding affinities. They were selected for chondrogenesis and qRT-PCR validation, and wogonin was experimentally demonstrated to have better chondrogenic differentiation effects in vitro. This study employed a multi-omics bioinformatics approach to identify CHAD as a potential hub gene of interest associated with osteoporosis. Preliminary in vitro experiments showed that wogonin modulates chondrogenic differentiation, a process related to CHAD’s function, suggesting potential avenues for further investigation into OP therapeutics.